FORMING DIGITAL CITIZENSHIP BASED ON AUGMENTED REALITY IN CIVIC EDUCATION LEARNING: A SYSTEMATIC LITERATURE REVIEW - Suriaman; Cecep Darmawan; Sapriya; Karim Suryadi; T Heru Nurgiansah; Karman (Jurnal Kewarganegaraan, 2026)
The swift advancement of digital technology necessitates a cohesive strategy to enhance digital citizenship within citizenship education via pertinent and contextual learning methodologies. Previous studies generally analyzed the two as separate factors; this study, however, rigorously investigates the level of integration between them in citizenship education. The study used a systematic literature review to analyze scientific articles published between 2018 and 2025, indexed in Scopus and Web of Science, using the keywords digital citizenship, augmented reality, citizenship education, learning, and technology, in accordance with PRISMA guidelines, assisted by Google Scholar and Publish or Perish. The findings indicate that digital citizenship through augmented reality serves as an immersive educational technology that enhances engagement and visualization in learning. The explicit integration of these two concepts remains constrained. This paper presents a conceptual framework that designates augmented reality as a pedagogical intermediary for applying digital citizenship principles in experiential citizenship education, and advocates for more empirical validation in genuine educational settings.